Customer Interest in Gold Installment Financing: The Role of Promotion Strategy and Contract Implementation - Ayu Novita; Abdul Muiz Abdul Wadud Kasyful Anwar; Abdul Nasir (CIEBER: Contemporary Islamic Economic and Business Review, 2026)
The aim of this research has two main elements, the first is to find out the promotion strategy for gold installment financing products regarding customer interest at Bank Syariah Indonesia KCP Kuningan A Yani 1. Second, to find out the mechanism for implementing the contract. for gold installment financing products against customer interest at Bank Syariah Indonesia KCP Kuningan A Yani 1. This research is a type of field research using qualitative research methods and also using library research to complete the data. This research data was collected using observation, interviews and documentation. Based on the research results, it can be concluded that the promotional strategy implemented by BSI KCP Kuningan A Yani 1 includes various approaches. The debut strategy includes direct promotion through canvassing, namely, holding meetings and presentations to agencies. Apart from that, there is also an open table strategy, where product offers are made directly to customers who make transactions with customer service. Bank Syariah Indonesia implements the STP (Segmentation, Targeting, Positioning) marketing strategy and marketing mix such as 4P (product, price, place, promotion). The contract used is murabahah as a form of sale and purchase and rahn as binding collateral. This promotional strategy analysis is carried out using the SWOT method (strengths, weaknesses, opportunities, threats) to determine the strengths, weaknesses, opportunities and threats faced.